2019
DOI: 10.1155/2019/6980208
|View full text |Cite
|
Sign up to set email alerts
|

Burden, Positive Aspects, and Predictive Variables of Caregiving: A Study of Caregivers of Patients with Pediatric Glaucoma

Abstract: Purpose. To determine the presence of burden and positive aspects among caregivers of patients with pediatric glaucoma (PG) and to establish whether they were influenced by the characteristics of the caregivers and the patients. Method. This study was designed to be cross-sectional and descriptive. The Chinese version of the Caregiver Burden Inventory (CBI) and the Positive Aspects of Caregiving (PAC) questionnaires were used to evaluate the caregivers. The demographic data of the enrolled participants were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Zhu et al (2019) found no correlation between demographic data and PAC scores [ 16 ]. There were, however, correlations between demographic data and CBI scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al (2019) found no correlation between demographic data and PAC scores [ 16 ]. There were, however, correlations between demographic data and CBI scores.…”
Section: Resultsmentioning
confidence: 99%
“…Caregiving for this complex disease presents significant emotional, social, and financial challenges. Aggregate results from this review indicate that the caregiver’s female gender, employment status, and longer duration of disease reduce caregivers’ QoL and increase caregiver burden [ 16 , 17 , 21 ]. Individual studies have also found that lower level of education, lower household income, caregiving for other children with glaucoma, and the child’s older age and poorer visual acuity adversely impact these measures of caregiver wellbeing [ 16 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that the health-related effects of care on caregivers' lives are positively influenced by factors such as income and social support [26] . Low-income carers are considered to belong to a vulnerable group [27] . Factors such as loss of income, cost savings and working hours can lead to a shift away from most social and daily activities, resulting in greater caregiver distress [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with childhood glaucoma present within 6 months of birth with ∼ 80% appearing before 1 year of age (11). Childhood glaucoma and its management not only have a marked impact on functional vision of children, but also reduced the quality of life of the patients, relatives, and caregivers (12)(13)(14). Hence, early diagnosis is crucial for children affected with glaucoma to receive timely and appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%